(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This research aimed to determine why is kebaya often used in wedding ceremony and what is the reason they choose the modern kebaya.This research method was used descriptive qualitative, which give descriptive about why is kebaya often used in wedding ceremony and what is the reason they choose the modern kebaya.The result showed that most of the people in north luwu still keep kebaya as an obligation in every wedding ceremony. They admit kebaya means politeness in every ceremony.